COVID-19 in individuals adapted to aerobic exercise - Tretyakov, A. Yu.; Zakharchenko, S. P.; Romasenko, L. V.; Dyatlova, A. V.; Zhabskaya, A. V.; Ermilov, O. V.; Tret'yakov, M. A.; Chentsova, D. D. (Pulmonologiya, 2020)
Analysis of COVID-19 features in individuals who regularly practice aerobic training. Methods. Asymptomatic persons and patients with COVID-19 older than 30 years, 293 people (180 men and 113 women), 214 of them - inhabitants of the Moscow region (the beginning of the sampling - 2nd decade of April 2020) and 79 - inhabitants of the Belgorod region (the beginning of the sampling - 2nd decade of May 2020), adapted (27 people - 1st group) and unadapted (266 - control group) to aerobic training (AT). Computer tomography of the chest, RNA test for SARS-CoV-2 in smears from the nasopharynx-oropharynx, the clinical blood sample and level of antibodies to SARS-CoV-2 were studied. The criterion for adaptation to aerobic loads was considered compliance with the rules of the American Heart Association, 2008. Results. Adapted to AT individuals, in contrast to the control group, characterized with the prevalence of asymptomatic (p = 0.045) and absence of severe forms of COVID-19, limited cataral simptoms of the disease (p < 0.001), rare pneumonia with absence (1) or presence (2) of acute respiratory failure (p1 = 0,028; p2 = 0,034), along with lower prevalence of diseases, potentiating this infection (p = 0.03). Conclusion. Patients adapted to AT have less severe course of COVID-19.